Judges’ Considerations in the Case Judgment of Premarital Sex Crime with Underage Child Based on Mutual Love at the Bengkulu District Court - Kurnia Dewi Anggraeny Kurnia Dewi Anggraeny; Oktafia Nur Alimah; Gatot Sugiharto; Salsabila Nurussa’adah (Jurnal Jurisprudence, 2023)
ABSTRACT Purpose: This research aims to analyze the form of liability that can be imposed on child perpetrators for criminal acts of premarital sex with an underage child based on mutual love. Furthermore, this research aims to analyze the juridical and non-juridical considerations and the verdict of the judge in sentencing the child perpetrators for a premarital sex crime with an underage child in Bengkulu Court Judgment No. 20/Pid.Sus-Anak/2021/PN Bgl and No. 35/Pid.Sus-Anak/2022/PN Bgl. Methodology: This research used normative legal research. The approach method employed in this research was a juridical approach, referring to the applicable laws and regulations. The analysis of legal materials in this research utilized a qualitative method, i.e., a step to describe the data obtained in sentence form. Results: The results demonstrated that a child who committed criminal acts of premarital sex with an underage child based on mutual love can still be held criminally liable. The form of liability imposed on child perpetrators is imprisonment, but the special minimum provisions of imprisonment do not apply. Judges' Considerations in the Bengkulu District Court Judgment No. 20/Pid.Sus-Anak/2021/PN Bgl and No. 35/Pid.Sus-Anak/2022/PN Bgl are for the fact that there were non-juridical causalities of criminal acts of premarital sex with an underage child or sexual intercourse due to the romantic relationships between the victim and the perpetrator whose intercourse was consensual and did not always involve force or violence. These non-juridical considerations were made by the judge as mitigating circumstances for child perpetrators. Benefits: This research can be used as reference material for the government and law enforcers, particularly judges, in deciding a case of premarital sex with an underage child committed by a child based on mutual love. Thus, law enforcement against child perpetrators of sexual abuse would become more impartial, and child victims would also receive attention and protection. Novelty/Originality: Regarding the analysis of the judge’s considerations in Judgment No. 20/Pid.Sus-Anak/2021/PN Bgl and No. 35/Pid.Sus-Anak/2022/PN Bgl on criminal liability for the child perpetrator of premarital sex with an underage child based on mutual love, the existing Law on Child Protection (UUPPA) has not comprehensively regulated the form of liability for child perpetrator of the premarital sex crime with underage children based on mutual love and non-juridical causality of the premarital sex crime with underage children. Keywords: obscenity, children, consensual, mutual love  Abstrak  Tujuan: Penelitian ini bertujuan untuk menganalisis bentuk tanggung jawab yang dapat dikenakan pada pelaku anak-anak untuk tindakan kriminal seks pra-perkawinan dengan anak di bawah umur berdasarkan cinta bersama. Selain itu, penelitian ini bertujuan untuk menganalisis pertimbangan-pertimbangan hukum dan non-judi dan putusan hakim dalam menghukum pelaku kejahatan seksual pra-perkawinan dengan anak di Pengadilan Bengkulu Keputusan No. 20/Pid.Sus-Anak/2021/PN Bgl dan No. 35/Ped. Metodologi: Penelitian ini menggunakan penelitian hukum normatif. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan hukum, mengacu pada hukum dan peraturan yang berlaku. Analisis materi hukum dalam penelitian ini menggunakan metode kualitatif, yaitu, langkah untuk menggambarkan data yang diperoleh dalam bentuk kalimat. Hasil: Hasilnya menunjukkan bahwa seorang anak yang melakukan tindakan kriminal seks pra-perkawinan dengan seorang anak di bawah umur berdasarkan cinta bersama masih dapat ditanggung kejahatan. Bentuk tanggung jawab yang dikenakan pada pelaku anak adalah penjara, tetapi ketentuan minimum khusus penjara tidak berlaku. Pertimbangan hakim dalam putusan Pengadilan Distrik Bengkulu No. 20/Pid.Sus-Anak/2021/PN Bgl dan No. 35/PID.Sust-Anak/2022/PNBgl adalah atas fakta bahwa ada kausal-kausal non-hukum dari tindakan kejahatan seks pra-perkawinan dengan anak di bawah umur atau hubungan seksual karena hubungan romantis antara korban dan pelakunya yang hubungan itu konsensual dan tidak selalu melibatkan kekuatan atau kekerasan. Pertimbangan-pertimbangan non-hukum ini dibuat oleh hakim sebagai keadaan meringankan bagi pelaku anak. Manfaat: Penelitian ini dapat digunakan sebagai bahan referensi bagi pemerintah dan penegak hukum, terutama hakim, dalam memutuskan kasus seks pra-perkawinan dengan anak yang masih kecil yang dilakukan oleh anak berdasarkan cinta bersama. Dengan demikian, penegakan hukum terhadap pelaku pelecehan seksual anak akan menjadi lebih adil, dan anak-anak korban juga akan menerima perhatian dan perlindungan. Novelty dan Originality: Berkaitan dengan analisis pertimbangan hakim dalam Keputusan No. 20/Pd.Sus-Anak/2021/PN Bgl dan No. 35/Pid.Sust-Anak/2022/PNBgl tentang tanggung jawab pidana bagi anak yang melakukan hubungan seksual pra-perkawinan dengan anak di bawah umur atas dasar cinta bersama, Undang-Undang Perlindungan Anak (UUPPA) saat ini belum secara komprehensif mengatur bentuk tanggung jawab anak-anak yang melakukan kejahatan seks pra-Perkawinan terhadap anak di atas usia di atas umur berdasarkan cinta bersama dan kausalitas non-juridis dari hubungan seksual di bawah usia.  Kata kunci: obscenity, anak-anak, konsensual, cinta bersama